Hybrid separator and electrochemical device including same

By coating the nitrile-based compound and lithium salt layer of the porous substrate on the separator of the electrochemical device, and changing its phase into liquid or gel state by heating, the heat resistance and impregnation speed of the electrochemical device are solved, and the problem of heat resistance and impregnation speed is achieved. Improved safety and capacity.

CN119315217APending Publication Date: 2025-01-14SK INNOVATION CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410927635.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-14
Filing Date
2024-07-11
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Existing electrochemical devices are prone to internal short circuits under high temperatures and impacts, resulting in fires and explosions. The electrolyte impregnation speed is slow and the manufacturing process is complicated. It is necessary to improve the heat resistance and safety of the diaphragm to simplify the process.

Method used

Using porous substrates as separator material, different nitrile compound and lithium salt solid phase layers are coated on both sides, and by heating, they are melted and changed to liquid or gel state, thereby playing the role of electrolytes and reducing the amount of electrolytes alone. Rely on and increase the impregnation speed of the electrolyte.

Benefits of technology

It achieves the prevention of electrical short circuits and fires caused by nail penetration under 100% charging state, improves battery capacity and safety, simplifies manufacturing processes, and provides high ionic conductivity and interface stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315217A_ABST
    Figure CN119315217A_ABST
Patent Text Reader

Abstract

The invention relates to a hybrid separator and an electrochemical device comprising the same. More specifically, the present invention can provide an electrochemical device having improved flame retardancy and safety, and relates to a hybrid separator easy to store and transport, and an electrochemical device including the same. More specifically, the present invention relates to a new-concept hybrid separator comprising a functional coating layer formed in a solid state at room temperature, in order to manufacture a battery, when an electrode and the hybrid separator face each other and are heated, the functional coating layer is formed in a solid state at room temperature. The solid functional coating layers coated on both surfaces of the separator are melted and mixed to satisfy specific content ratio conditions, so that the separator can be phase-changed into a liquid state or a gel state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hybrid diaphragm and an electrochemical device comprising the hybrid diaphragm. Background Art

[0002] In recent years, in order to be applied to electric vehicles and energy storage devices, it is necessary to realize the large capacity of electrochemical devices. As the capacity of electrochemical devices increases, the risk of fire and explosion also increases, so the heat resistance and safety of electrochemical devices are more needed. In addition, as the capacity increases, the internal impregnation of the electrolyte becomes more difficult during the injection of the electrolyte, so it is necessary to increase the impregnation speed of the electrolyte and simplify the manufacturing process.

[0003] In conventional electrochemical devices, a battery is manufactured by winding a cell consisting of a negative electrode, a positive electrode, and a separator between the negative electrode and the positive electrode into a cylinder or stacking them, inserting them into a soft pack, and injecting a liquid electrolyte into the soft pack. The electrolyte plays a role in enabling smooth movement of charges between electrodes, and generally includes a solvent and a salt.

[0004] As for the separator used in electrochemical devices, internal short circuit may be caused due to shrinkage at high temperature or penetration caused by external impact, and fire may occur due to the internal short circuit. Therefore, for the safety of users, the thermal stability and penetration safety of the separator are issues that must be improved. In particular, since lithium secondary batteries use electrolytes containing non-aqueous organic solvents with low flash points as main components, there is a possibility of fire and explosion when overcharged or impact or penetration occurs, so it is necessary to improve it.

[0005] In recent years, attempts have been made to ensure penetration safety by applying a highly heat-resistant separator that improves the heat resistance of the separator. For this purpose, a method of improving battery safety by forming a coating layer containing an inorganic substance on an existing polyolefin-based film to improve the thermal stability of the separator is also used. Summary of the invention

[0006] 1. Technical issues to be resolved

[0007] According to one aspect of the present invention, an object is to provide a diaphragm having a porous substrate and a solid phase coating of any one or more selected from nitrile compounds and lithium salts formed on each surface of the porous substrate in different composition ratios, and the diaphragm can be rolled up during transportation.

[0008] In addition, the purpose is to provide a new type of hybrid membrane. When the membrane is used to assemble an electrochemical device, during the process of facing each other and heating and calendering with electrodes, the coatings formed on both sides of the porous substrate are heated, melted and mixed, so that the molar ratio of the components of the coating is different from that of the solid coating, thereby changing the phase to a liquid or gel state, so that it can play the role of an electrolyte.

[0009] Therefore, a novel hybrid separator that may not require the injection of a separate liquid electrolyte when manufacturing a battery can be provided, and an electrochemical device that can increase the electrolyte impregnation speed and simplify the manufacturing process by adopting such a hybrid separator can be provided. That is, the purpose is to provide a battery and a manufacturing method thereof as an electrochemical device that can increase the electrolyte impregnation speed and simplify the manufacturing process.

[0010] In addition, according to another aspect of the present invention, an electrochemical device that can prevent fire and explosion by using a hybrid separator according to an embodiment is provided. More specifically, an electrochemical device that can improve the heat resistance and safety of a lithium secondary battery and the hybrid separator is provided.

[0011] In addition, an object is to provide a novel hybrid separator and an electrochemical device including the hybrid separator, wherein the hybrid separator can prevent electrical short circuit and the resulting fire and explosion during nail penetration evaluation at a charge state of less than 100% and a charge state of 100%.

[0012] Furthermore, the aim is to provide a higher battery capacity when producing batteries of the same volume.

[0013] The hybrid membrane of the present invention and the electrochemical device including the hybrid membrane can be widely used in electric vehicles, battery charging stations, other green technology fields such as solar power generation and wind power generation using batteries. In addition, the hybrid membrane of the present invention and the electrochemical device including the hybrid membrane can be used in eco-friendly electric vehicles and hybrid vehicles, etc., to prevent climate change by suppressing air pollution and greenhouse gas emissions.

[0014] (II) Technical solution

[0015] According to the present invention, a hybrid membrane is provided, which includes: a porous substrate; a first functional layer, which is formed by coating a single nitrile compound or a mixture of a nitrile compound and a lithium salt on one side of the porous substrate, and the first functional layer is a solid phase; and a second functional layer, which is formed by coating a mixture of a nitrile compound and a lithium salt on the other side of the porous substrate, and the second functional layer is a solid phase, wherein the contents of lithium salt in the first functional layer and the second functional layer are different from each other.

[0016] As an embodiment, the content of the lithium salt is different from each other, which also includes the case where the first functional layer does not contain a lithium salt, that is, the content of the lithium salt is 0.

[0017] For example, as a first embodiment, the first functional layer may not contain a lithium salt and may be composed of a single nitrile compound, and the second functional layer may be composed of a mixture of a nitrile compound and a lithium salt. As a second embodiment, the first functional layer and the second functional layer may each be composed of a mixture of a nitrile compound and a lithium salt, and the contents of the lithium salt contained in the first functional layer and the second functional layer may be different from each other.

[0018] As an embodiment, the first functional layer and the second functional layer may be formed by filling the surface and pores of the porous substrate.

[0019] As an embodiment, the first functional layer and the second functional layer are in a solid phase at room temperature, but when heated, the solid first functional layer and the second functional layer melt and mix and undergo a phase change, thereby maintaining a liquid phase or a gel phase at room temperature.

[0020] As an embodiment, after the phase change sample is placed in a quartz cell of 10×40×50 mm and left at room temperature for 12 hours, the haze is measured using a colorimeter (COH400, Nippon denshoku) at a vertical distance of 100 mm from a halogen lamp with a rated voltage of 12 V and a power consumption of 50 W. The haze of the liquid phase can be less than 50%, the haze of the gel phase can be more than 50% and less than 90%, and the haze of the solid phase can be more than 90%.

[0021] As an embodiment, the nitrile compound is solid at room temperature or can exist as a solid at room temperature when mixed with a lithium salt, and the nitrile compound can be a compound containing one or more -C≡N functional groups.

[0022] As an embodiment, the nitrile-based compound which is solid at room temperature can be any one selected from succinonitrile (SN), (3,4-dimethoxyphenyl)acetonitrile, 2-(4-bromo-2-methoxyphenyl)acetonitrile, 2-fluorophenylacetonitrile, 2-chloro-4-fluorophenylacetonitrile and 4-fluorophenylacetonitrile, or a mixture of two or more thereof.

[0023] The nitrile compound that can exist as a solid at room temperature when mixed with a lithium salt can be any one selected from glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, sebacatenitrile, undecane dinitrile, dodecane dinitrile, etc., or a mixture of two or more thereof, and is not limited thereto.

[0024] As an embodiment, the lithium salt may be selected from LiTFSI ((CF3SO2)2NLi), LiFSI ((SO2F)2NLi), (C2F5SO2)2NLi, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)3CLi, LiBF2(C2O4), LiAlO2 and LiN(C x F 2x+ 1SO2)(C y F 2y+1 SO2) etc., wherein x and y may be natural numbers and are not limited thereto.

[0025] As an embodiment, the total content of the nitrile compound used in the first functional layer and the second functional layer may be such a content that a liquid phase or a gel phase is maintained at room temperature when mixed with a lithium salt.

[0026] As an embodiment, the nitrile-based compound may be succinonitrile, the lithium salt may be LiFSI, and the weight ratio of the total content of succinonitrile used in the first and second functional layers relative to LiFSI may be 2 to 7, and is not limited thereto.

[0027] As an embodiment, the first functional layer may consist of succinonitrile alone, and the second functional layer may consist of a mixture of LiFSI:succinonitrile in a weight ratio of 1:1 to 1:1.5 or 1:10, and is not limited thereto.

[0028] As an embodiment, the coating amounts of the first and second functional layers may be adjusted such that a total content of succinonitrile used in the first and second functional layers is in a ratio of 2 to 7 by weight relative to LiFSI, and is not limited thereto.

[0029] As an embodiment, the first functional layer may be formed by impregnation to the surface and the first side of the porous substrate, and may be formed to be 0.5-10 g / m 2 The second functional layer may be formed by impregnation to the surface and the second surface of the porous substrate, and may be formed to 0.5-10 g / m 2 , and are not limited to this.

[0030] As an embodiment, the porous substrate may be formed by laminating any one or more selected from a porous film, a nonwoven fabric, and a woven fabric, but is not limited thereto.

[0031] As an embodiment, the thickness of the porous substrate may be 1-80 μm, and is not limited thereto.

[0032] As an embodiment, the first functional layer and the second functional layer may further include less than 5 wt % of a carbonate-based additive, and are not limited thereto.

[0033] According to the present invention, an electrochemical device is provided, which includes a hybrid membrane of one embodiment, wherein the hybrid membrane is set and heated so that the first functional layer and the second functional layer included in the hybrid membrane are liquefied and mixed with each other and undergo a phase change, thereby existing as a phase change layer in a liquid phase or a gel phase at room temperature.

[0034] As an embodiment, by arranging the hybrid separator between the positive electrode and the negative electrode and heating, the first functional layer and the second functional layer included in the hybrid separator are liquefied and mixed with each other and undergo a phase change, thereby being present as a phase change layer in a liquid phase or a gel phase at room temperature. It is recorded that as a conventional electrochemical device, the separator can be arranged between the negative electrode and the positive electrode, but it is not necessarily limited to this. As long as it can play the role of the separator, its stacked structure is not limited.

[0035] As an embodiment, the capacity of the electrochemical device may be 50 mAh or more, but is not limited thereto.

[0036] According to the present invention, a method for manufacturing a hybrid membrane is provided, the method comprising the following steps: coating a single solid-phase nitrile compound or a solid-phase mixture of a nitrile compound and a lithium salt on a first surface of a porous substrate in a state where the nitrile compound is heated to be melted so as to be impregnated into the surface and the inside of the pores, and cooling to form a solid-phase first functional layer; and coating a solid-phase mixture of a nitrile compound and a lithium salt on a second surface of the porous substrate in a state where the nitrile compound is heated to be melted so as to be impregnated into the surface and the inside of the pores, and cooling to form a solid-phase second functional layer, wherein the contents of lithium salt in the first functional layer and the second functional layer are different from each other.

[0037] As an embodiment, the first functional layer and the second functional layer are in a solid phase at room temperature, but when heated, the solid first functional layer and the second functional layer melt and mix and undergo a phase change, thereby maintaining a liquid phase or a gel phase at room temperature.

[0038] As an embodiment, the first functional layer and the second functional layer may further include less than 5 wt % of a carbonate-based additive, and are not limited thereto.

[0039] As an embodiment, the nitrile-based compound may be succinonitrile, the lithium salt may be LiFSI, and the weight ratio of the total content of succinonitrile used in the first and second functional layers relative to LiFSI may be 2 to 7, and is not limited thereto.

[0040] (III) Beneficial effects

[0041] The hybrid separator according to one embodiment of the present invention has excellent flame retardancy and can provide a safety effect against fire when a short circuit occurs due to penetration.

[0042] In addition, the hybrid diaphragm is not affected by the thermal history when it is applied to each surface of the porous substrate to form a coating, so the coating exists in a solid phase. Since the coating is in a solid state, it can be wound after manufacturing the hybrid diaphragm, and can be transported in a wound state during transportation. However, when the hybrid diaphragm and the electrode are facing each other and heated and rolled to manufacture the battery, the substances coated on each surface of the porous substrate melt and mix, and phase change to a single-phase liquid phase or gel phase with a different composition ratio from the components of each coating, thereby playing the role of a fluid electrolyte. Therefore, when the battery is manufactured by stacking the hybrid diaphragm with the electrode and being affected by the thermal history, the liquid phase or gel phase of the phase change can play the role of an electrolyte, thereby providing an electrochemical device that does not require the injection of a separate liquid electrolyte. The coating used in the hybrid diaphragm has a high flash point and a low vapor pressure, and does not require the injection of a separate liquid electrolyte, so that the safety of the battery and the occurrence of fire problems can be suppressed. Therefore, when an electrochemical device such as a battery is manufactured using the hybrid separator, an electrochemical device that can prevent electrical short circuits and the resulting fire and explosion during nail penetration evaluation at a charge state of less than 100% as well as a charge state of 100% can be provided.

[0043] The coating of the hybrid separator is coated with a substance that is solid at room temperature, such as 20-35°C, which is not affected by a single thermal history, but can be melted and phase-changed to a liquid phase or a gel phase when heated, such as above 35°C, above 40°C, above 50°C, or 60-80°C. However, the layers of the coatings coated on both sides of the porous substrate are components with different composition ratios from each other, and each coating is solid at room temperature, such as 20-35°C, but in a state where the coatings coated on each side are melted and mixed, they no longer exist in a solid phase even at room temperature, but in a liquid phase or a gel phase. Therefore, it can become a new concept hybrid separator, and before assembling the battery, the hybrid separator itself is a solid laminate, so that it can be wound on a roller and is easy to transport, and when assembling the battery, there is no need to inject a separate liquid electrolyte process, and the coating acts as an electrolyte, so the electrolyte impregnation speed can be increased. However, although it is not excluded to manufacture a battery using the hybrid separator and further inject a separate liquid electrolyte, the content of the added liquid electrolyte may be an amount significantly reduced compared with the content injected into the existing battery.

[0044] In addition, since the phase changes to a liquid phase or a semi-solid gel phase, the interface stability between the active material of the electrode and the electrolyte can be ensured.

[0045] Furthermore, the hybrid separator according to one embodiment of the present invention and the electrochemical device including the hybrid separator may provide high ion conductivity, excellent process efficiency and interface stability, impact resistance, high heat resistance, and excellent flame retardancy.

[0046] According to one embodiment of the present invention, an electrochemical device with improved flame retardancy and penetration safety can be provided, and a hybrid membrane and an electrochemical device including the hybrid membrane can be provided. As for the hybrid membrane, when assembling the battery, the coating acts as an electrolyte, thereby increasing the electrolyte impregnation speed and simplifying the manufacturing process, and it is easy to store and transport. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The photographs are taken to observe the state at room temperature (RT) based on the mixing ratio of succinonitrile (SN) and lithium salt (LiFSI) used for coating on the separator according to one embodiment.

[0048] Figure 2 is a cross-sectional view showing one embodiment of a hybrid separator, and shows a cross section of the hybrid separator in which a first functional layer and a second functional layer are formed.

[0049] Figure 3 One embodiment of manufacturing a battery is shown, and is a cross-sectional view showing that a hybrid separator according to one embodiment is provided between a negative electrode and a positive electrode.

[0050] Figure 4 An embodiment of manufacturing a battery is shown, and a cross-sectional view is shown in which a mixed separator according to an embodiment is set between the negative electrode and the positive electrode and then heated so that the first functional layer and the second functional layer are melted and mixed to form a phase change layer that exists in a liquid phase or a semi-solid gel phase at room temperature (RT).

[0051] Figure 5 The figures show explosion and non-explosion in a nail penetration test of a battery. DETAILED DESCRIPTION

[0052] The present invention is described in detail below, but this is merely exemplary, and the present invention is not limited to the specific embodiments described exemplarily.

[0053] In addition, unless otherwise defined, all technical terms and scientific terms have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the description of the present invention are only used to effectively describe specific embodiments and are not intended to limit the present invention.

[0054] Furthermore, unless otherwise specifically stated herein, singular forms used in the specification and the claims may also include plural forms.

[0055] Furthermore, unless otherwise specifically described to the contrary, when a part is described as “including” or “comprising” a certain component, it means that other components may also be included, rather than excluding other components.

[0056] In addition, unless specifically defined otherwise, when a layer or component is described as being “on” another layer or component, this includes not only the case where the layer or component is in contact with the other layer or component but also the case where another layer or component exists between the two layers or components.

[0057] In addition, "about", "substantially", etc. are used to mean numerical values ​​or values ​​close to them when inherent manufacturing and material tolerances occur in the meanings involved, and are used to prevent the disclosure of precise or absolute numerical values ​​to aid understanding of the present invention from being unfairly used by unscrupulous infringers.

[0058] In the present invention, "normal temperature" refers to the conventional temperature during storage and transportation of the separator and the electrochemical device, for example, it may be 20-35°C.

[0059] In the present invention, in "the solid first functional layer and the second functional layer melt and mix and undergo phase change when heated", the heating refers to a temperature higher than the normal temperature. That is, the heating refers to a temperature at which the solid phase undergoes phase change by heating using a separate heating method. For example, it may be above normal temperature, above 35°C, above 40°C, above 50°C, or 60-80°C.

[0060] One embodiment of the present invention provides a hybrid membrane, comprising: a porous substrate; a first functional layer, the first functional layer is formed by coating a single nitrile compound or a mixture of a nitrile compound and a lithium salt on one side of the porous substrate, and the first functional layer is a solid phase; and a second functional layer, the second functional layer is formed by coating a mixture of a nitrile compound and a lithium salt on the other side of the porous substrate, and the second functional layer is a solid phase, wherein the contents of the lithium salt in the first functional layer and the second functional layer are different from each other. As an embodiment, the contents of the lithium salt are different from each other also include the meaning that the first functional layer does not contain a lithium salt.

[0061] For example, as a first embodiment, the first functional layer may not contain a lithium salt and may be composed of a single nitrile compound, and the second functional layer may be composed of a mixture of a nitrile compound and a lithium salt. As a second embodiment, the first functional layer and the second functional layer may each be composed of a mixture of a nitrile compound and a lithium salt, and the contents of the lithium salt contained in the first functional layer and the second functional layer may be different from each other.

[0062] As an embodiment, the first functional layer and the second functional layer may be formed by filling the surface and pores of the porous substrate.

[0063] As an embodiment, the first functional layer and the second functional layer may be formed to be 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, 90% or more, or 95% or more relative to the total area of ​​the porous substrate, and may substantially be formed in the range of 100%, and may have an area between the above values. For example, it may be formed to be 80-100%, and may substantially be formed on the entire area, and is not limited thereto.

[0064] As an embodiment, the first functional layer and the second functional layer are in a solid phase at room temperature, for example, at 20-35°C, but when heated to a temperature above room temperature, the solid first functional layer and the second functional layer melt and mix with each other, and the composition of the components of each layer changes, so even if the temperature returns to a lower room temperature, it will not change into a solid phase, but can remain in a liquid phase or a gel phase as it is. At this time, the heating temperature is not limited, as long as it is a temperature that does not affect the pores of the diaphragm of the present invention and can melt and mix the coatings applied on both sides, for example, it can be more than 35°C, above 40°C, 35-80°C, 40-80°C or 60-80°C.

[0065] The liquid phase, gel phase or solid phase can be evaluated visually, but can also be measured by the following method. That is, after the phase-changed sample is placed in a quartz cell of 10×40×50 mm and left at room temperature for 12 hours, the haze is measured by using a colorimeter (COH400, Nippon Denshoku Industries Co., Ltd.) and vertically separated by 100 mm from a halogen lamp with a rated voltage of 12 V and a power consumption of 50 W. The haze of the liquid phase can be 50% or less or 0-50%, the haze of the gel phase can be more than 50% and less than 90%, and the haze of the solid phase can be more than 90% or 90-100%.

[0066] Hereinafter, each component of the present invention will be described in more detail.

[0067] [Nitrile compounds]

[0068] As an embodiment, the nitrile compound refers to a compound that is solid at room temperature and contains one or more -C≡N functional groups. In addition, even if it is not solid at room temperature alone, as long as it can exist as a solid at room temperature when mixed with a lithium salt, it can be used without limitation.

[0069] The examples of the nitrile compound are not particularly limited, as long as they are nitrile compounds having a melting point of more than 35°C or 40°C, but for example, they may be selected from any one or a mixture of two or more of succinonitrile (SN), (3,4-dimethoxyphenyl)acetonitrile, 2-(4-bromo-2-methoxyphenyl)acetonitrile, 2-fluorophenylacetonitrile, 2-chloro-4-fluorophenylacetonitrile and 4-fluorophenylacetonitrile, etc., and may be replaced by other constituent elements as long as they do not depart from the scope of the present invention. Specifically, succinonitrile (SN) can be used from the viewpoint of imparting flame retardancy and providing a battery with a higher capacity at room temperature.

[0070] Alternatively, the nitrile compound may be a solid compound at room temperature even if it is not solid at room temperature, but may exist as a solid compound when mixed with a lithium salt, for example, it may be a compound containing one or more -C≡N functional groups. For example, it may be any one or a mixture of two or more selected from glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelonitrile, sebacatenitrile, undecane dinitrile, dodecane dinitrile, etc., and may be replaced by other constituent elements as long as it does not depart from the scope of the present invention.

[0071] The nitrile compound can be included in the first functional layer and the second functional layer of the hybrid diaphragm of the present invention as a main coating component, except for the case where 100% of the nitrile compound is used as any coating of the two functional layers, when the nitrile compound is mixed with a lithium salt, specifically, based on the total weight of the coating solution used to form the first functional layer and the second functional layer, the content of the nitrile compound can be 50% by weight or more, 55% by weight or more, 60% by weight or more, 65% by weight or more, 70% by weight or more, 75% by weight or more, 80% by weight or more, 85% by weight or more, 90% by weight or more, 99.9% by weight or less, 95% by weight or less, 90% by weight or less, or any value between the above-mentioned numerical values. For example, it can be 50-99.9% by weight, 55-99.9% by weight, 60-90% by weight.

[0072] Within the above content range, excellent flame retardancy can be achieved, and the first and second functional layers formed on both sides of the separator can remain in a solid state at normal temperature to be easily transported.

[0073] [Ionizable lithium salt]

[0074] The lithium salt can be used without limitation as long as it is an ionizable lithium salt. For example, it can be selected from LiTFSI ((CF3SO2)2NLi), LiFSI ((SO2F)2NLi), (C2F5SO2)2NLi, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)3CLi, LiBF2(C2O4), LiAlO2 and LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) etc., wherein x and y may be natural numbers and are not limited thereto.

[0075] In addition, the lithium salt may include an imide lithium salt such as LiFSI. By including such an imide lithium salt, a strong and thin SEI film can be formed on the negative electrode.

[0076] As for the content of the lithium salt, as long as the lithium salt is mixed with the nitrile compound in each functional layer formed on each surface of the porous substrate and can exist in a solid phase at 10-35°C, but when the mixed membrane is heated to melt the functional layers and mix with each other, it no longer remains in a solid state at room temperature, for example, at the above-mentioned 10-35°C, but exists in a liquid phase or a gel phase, then its content is not limited.

[0077] As an embodiment, for example, based on the total weight of the coating solution used to form the first functional layer and the second functional layer, the content of the lithium salt may be less than 50% by weight, less than 49% by weight, less than 45% by weight, less than 40% by weight, less than 35% by weight, less than 30% by weight, less than 25% by weight, less than 20% by weight, less than 15% by weight, more than 10% by weight, or any value between the above values. For example, it may be 10-49% by weight, 10-45% by weight.

[0078] In the present invention, from the viewpoint that the coating can be applied in a solid phase and heated after the battery is manufactured to undergo a phase transition to a liquid phase or a gel phase, the total content of the nitrile compound used in the first functional layer and the second functional layer as a coating formed on each surface of the porous substrate can be a content that allows the nitrile compound to maintain a liquid phase or a gel phase at room temperature when mixed with a lithium salt.

[0079] As an embodiment, although not limited thereto, the nitrile compound may be succinonitrile, and the lithium salt may be LiFSI. The succinonitrile and LiFSI present a liquid phase, a gel phase, or a solid phase at room temperature according to the mixing ratio. In this regard, the phases according to the content ratios are more specifically illustrated in the manufacturing examples described later, and Figure 1 Photographs of each phase are shown in .

[0080] Hereinafter, as an embodiment, a case where succinonitrile is used as the nitrile compound and LiFSI is used as the lithium salt in the first functional layer and the second functional layer is described as an example.

[0081] As an embodiment, the total content of succinonitrile used in the first functional layer and the second functional layer may be 2 to 7 times the weight ratio of LiFSI, although not limited thereto. Figure 1 As shown, within the above range, the liquid phase or gel phase can be maintained after the phase change. In addition, when heating after manufacturing the battery, during the melting and mixing process, the phase change to the liquid phase or gel phase can be completely completed even at room temperature. By maintaining the liquid phase or gel phase at room temperature, the capacity of the battery at room temperature can be ensured. In addition, within the above range, a battery with excellent flame retardancy and heat resistance can be provided.

[0082] As an embodiment, as a coating formed on each surface of the hybrid separator, the first functional layer may be composed of a single succinonitrile, and the second functional layer may be composed of a mixture of LiFSI: succinonitrile mixed in a weight ratio of 1:1 to 1:1.5 or a weight ratio of 1:10. Alternatively, the coating amount of the first functional layer and the second functional layer may be adjusted so that the total content of succinonitrile used in the first functional layer and the second functional layer is 2 to 7 relative to the weight ratio of LiFSI and formed. Within the above range, the coating of the hybrid separator remains in a solid phase, so it is easy to transport, and is melted and mixed with each other by heating when manufacturing the battery, and can be phase-changed into a liquid phase or a gel phase, but is not limited thereto.

[0083] As an embodiment, the first functional layer can be formed by impregnating the surface of the porous substrate and part or all of the pores inside the porous substrate, for example, the first functional layer can be formed to be 0.5-10 g / m 2 The second functional layer may be formed by impregnating the surface of the porous substrate and part or all of the pores inside the porous substrate, for example, 0.5-10 g / m 2, and is not limited thereto. At this time, the coating amounts of the first functional layer and the second functional layer may be the same or different from each other, and the coating amounts of each layer may be adjusted or the content of the lithium salt may be adjusted. As one aspect, the coating amount may be adjusted so that the total content of succinonitrile used in the first functional layer and the second functional layer is in a ratio of 2 to 7 relative to the weight ratio of the lithium salt (e.g., LiFSI).

[0084] As an embodiment, succinonitrile (SN) and an ionizable lithium salt are mixed with each other and transformed from a solid phase into a liquid phase or a gel phase. Below the melting point of SN, there is a para-cross isomer (para-cross-ortho-cross isomerism) relative to the central CC bond, and thus has ion conduction behavior. Therefore, it can act as an electrolyte. At this time, the trans isomer contributes to the aggravation of lattice defects and the reduction of activation energy for ion conduction, thereby improving ion mobility.

[0085] [Additional additives]

[0086] As an embodiment, the first functional layer and the second functional layer may further include a carbonate-based additive. Since the nitrile compound is solid at room temperature, the carbonate-based additive improves coating properties, and further improves the miscibility of the nitrile compound and lithium salts, and forms a more effective solid electrolyte interface (Solid Electrolyte Interphase, SEI) layer, from the above viewpoint, the carbonate-based additive can be used. Therefore, compared with the content of the solvent commonly used as a liquid electrolyte, it can be used with less content. For example, based on the gross weight of the coating solution for forming the first functional layer and the second functional layer, the content of the carbonate-based additive can be less than 5 weight %, 0.1 weight % or more and less than 5 weight %, 0.1-0.49 weight %. When the content of the carbonate-based solvent exceeds the above range, it may be difficult to form the first functional layer and the second functional layer with a solid phase on a porous substrate. In addition, from the viewpoint of being able to be wound on a roller for storage and transportation after manufacturing a diaphragm, it is preferably used with the above content range.

[0087] The carbonate-based additive may be, for example, any one selected from fluoroethylene carbonate (Fluoroethylene Carbonate, FEC), vinylene carbonate (Vinylene Carbonate, VC), vinylethylene carbonate (Vinylethylene Carbonate, VEC), ethylene carbonate (Ethylene carbonate, EC), propylene carbonate (Propylene carbonate, PC), difluoroethylene carbonate (DiFEC), etc., or a mixture of two or more thereof, and may be replaced by other constituent elements as long as it does not depart from the scope of the present invention.

[0088] In addition, as required, an additive commonly added to a liquid electrolyte used in the art may be further included. The content of the additive may be less than 5% by weight of the entire functional layer, but as long as the effect of the present invention is achieved, its content is not limited. As long as the additive is a known additive contained in a liquid electrolyte, it is not particularly limited, so further description is omitted.

[0089] [Porous substrate]

[0090] As an embodiment, the porous substrate may be formed by laminating any one or more of a porous film in the form of a polymer such as polyolefin, a non-woven fabric, and a woven fabric.

[0091] In addition, the porous substrate may be a porous substrate coated with ceramics, wherein a ceramic layer in which inorganic particles are connected to each other to form pores is stacked on one or both sides of a porous film, nonwoven fabric, and woven fabric formed of a polymer such as polyolefin, polyester, polyimide, polyamide, polyamideimide, polysulfone, polyketone, polyurethane, polyether, etc., but is not limited thereto. As an example, the porous substrate may be a polyimide nonwoven fabric, and is not limited thereto.

[0092] As an embodiment, in order to further improve the coating and impregnation properties of the composition for forming the first functional layer and the second functional layer, the porous substrate may be surface treated. For example, in the presence of oxygen or air, hydrophilic treatment may be performed by plasma, arc discharge, and the like, but is not limited thereto.

[0093] The average pore size of the porous substrate is measured by peeling off the polyethylene layer from the multilayer separator and using a pore size analyzer (porometer: CFP-1500-AEL of PMI) according to ASTM F316-03 and using a semi-dry method. In order to measure the pore size, Galwick liquid (surface tension: 15.9 dyne / cm) provided by PMI can be used, but it is not limited thereto.

[0094] The thickness of the porous substrate may be 1-80 μm, but is not limited thereto. The thickness of the porous substrate may be obtained by measuring the thickness of 10 layers of separators using a contact micrometer (Mitutoyo, Japan) and then calculating the average value divided by 10.

[0095] [Method for manufacturing hybrid separator]

[0096] Hereinafter, a method for producing the hybrid separator of the present invention will be described with examples.

[0097] As an embodiment, the method includes the following steps: coating a single solid phase nitrile compound or a solid phase mixture of a nitrile compound and a lithium salt on a first surface of a porous substrate while heating it to make it melt, and cooling it to form a first functional layer of a solid phase in which the single compound or the mixture is impregnated into the surface of the first surface and the inside of the pores; and coating a solid phase mixture of a nitrile compound and a lithium salt on a second surface of the porous substrate while heating it to make it melt, and cooling it to form a second functional layer of a solid phase in which the mixture is impregnated into the surface of the second surface and the inside of the pores, wherein the contents of lithium salt in the first functional layer and the second functional layer may be different from each other.

[0098] As an embodiment, the first functional layer and the second functional layer are in a solid phase at room temperature, but when heated, the solid first functional layer and the second functional layer melt and mix and undergo a phase change, thereby transforming into a phase change layer, which can also maintain a liquid phase or a gel phase at room temperature.

[0099] As an embodiment, the first functional layer and the second functional layer may further include a carbonate-based additive, and may further include less than 5 wt % of the carbonate-based additive, but is not limited thereto.

[0100] In addition, the first functional layer and the second functional layer of the coating layer may be substantially free of solvent, and may further contain less than 5 wt % of solvent from the viewpoint of easier coating. The solvent may be a carbonate-based solvent.

[0101] When the first functional layer and the second functional layer are coated, the melting temperature of the mixture thereof may be, for example, more than 35°C, more than 40°C, or 60-80°C. In addition, it may be heated to the above temperature and coated. The coating method is not limited as long as it is a method commonly used in the art, and may be coating or dipping. In addition, when coating, it may be coated on the entire surface of the porous substrate, for example, relative to the area of ​​the porous substrate, it may be coated in a range of more than 50%, more than 60%, more than 70%, more than 80%, more than 85%, more than 90%, more than 95%, substantially in a range of 100%, and may have a coating area between the above values, preferably, it may be coated in an area of ​​80-100%, and is not limited thereto.

[0102] In the case of the hybrid separator manufactured by the method as described above, the first functional layer and the second functional layer exist in a solid state at normal temperature, and thus can be stored and transported after being rolled up.

[0103] In addition, when manufacturing a battery, or in the step of placing the mixed separator between the negative electrode and the positive electrode and heating and pressurizing to manufacture the battery, the first functional layer and the second functional layer can be melted and mixed with each other and undergo phase change. The functional layer coated on each surface of the porous substrate exists in a solid phase, melts and mixes and undergoes a phase change. Even if it is cooled to room temperature after the phase change, it will not return to the solid phase, but can maintain a liquid phase or a gel phase. The heating temperature can be, for example, more than 35°C, more than 40°C, more than 50°C, more than 60°C, less than 80°C, and temperatures therebetween. Therefore, there may be no need for a separate process of injecting a liquid phase electrolyte, and the phase changes from a solid state to a liquid phase or a gel phase, so that the impregnation and adhesion of the active material of the electrode can be improved, and excellent ionic conductivity can be provided. In addition, a battery with excellent flame retardancy can be provided, and in particular, a very safe battery that does not catch fire even when 100% charged in a penetration evaluation can be provided.

[0104] [Electrochemical Devices]

[0105] The electrochemical device according to one embodiment of the present invention may be a lithium secondary battery, and is not limited thereto.

[0106] As an embodiment, as an electrochemical device including a hybrid separator according to an embodiment of the present invention, for example, by arranging the hybrid separator between the positive electrode and the negative electrode and heating, the first functional layer and the second functional layer included in the hybrid separator are mixed with each other and undergo a phase change, thereby also existing as a phase change layer in a liquid phase or a gel phase at room temperature. Therefore, a separate electrolyte may not be injected into the electrochemical device, but the electrolyte is not excluded.

[0107] As an embodiment, the capacity of the electrochemical device may be 50 mAh or more, 55 mAh or more, 60 mAh or more, 65 mAh or more, 70 mAh or more, 75 mAh or more, 80 mAh or more, and is not limited thereto.

[0108] The positive electrode may include a positive electrode collector and a positive electrode mixture layer disposed on at least one side of the positive electrode collector.

[0109] The positive electrode current collector may include stainless steel, carbon, nickel, aluminum, aluminum surface-treated with silver, titanium, or alloys thereof. The thickness of the positive electrode current collector may be, for example, 10-50 μm, but is not limited thereto.

[0110] The positive electrode mixture layer may include a positive electrode active material. The positive electrode active material may include a compound that can reversibly intercalate and deintercalate lithium ions.

[0111] According to an exemplary embodiment, the positive electrode active material may include lithium-nickel metal oxide. The lithium-nickel metal oxide may further include at least one of cobalt (Co), manganese (Mn), and aluminum (Al).

[0112] In some embodiments, the positive active material or the lithium-nickel metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 1.

[0113] [Chemical formula 1]

[0114] Li x Ni a M b O 2+z

[0115] In Chemical Formula 1, 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b≤0.4, and -0.5≤z≤0.1 may be satisfied. As described above, M may include Co, Mn, and / or Al.

[0116] The chemical structure represented by Chemical Formula 1 represents the bonding relationship contained in the layered structure or crystal structure of the positive electrode active material, and does not exclude other additional elements. For example, M may include Co and / or Mn, and Co and / or Mn may be provided together with Ni as the main active element of the positive electrode active material. Chemical Formula 1 is provided to represent the bonding relationship of the main active elements, and it should be understood that Chemical Formula 1 is a formula including the introduction and substitution of additional elements.

[0117] In one embodiment, in addition to the main active element, an auxiliary element for enhancing the chemical stability of the positive electrode active material or the layered structure / crystal structure may be further included. The auxiliary element may be mixed together into the layered structure / crystal structure to form a bond, and it should be understood that this case is also included in the chemical structure represented by Chemical Formula 1.

[0118] The auxiliary element may include, for example, at least one of Na, Mg, Ca, Y, Ti, Hf, V, Nb, Ta, Cr, Mo, W, Fe, Cu, Ag, Zn, B, Al, Ga, C, Si, Sn, Sr, Ba, Ra, P, or Zr. The auxiliary element may be an auxiliary active element that contributes to the capacity / power activity of the positive electrode active material together with Co or Mn, such as Al.

[0119] For example, the positive active material or the lithium-nickel metal oxide may include a layered structure or a crystal structure represented by the following Chemical Formula 1-1.

[0120] [Chemical formula 1-1]

[0121] Li x Ni a M1 b1 M2 b2 O 2+z

[0122] In Chemical Formula 1-1, M1 may include Co, Mn and / or Al. M2 may include the auxiliary elements described above. In Chemical Formula 1-1, 0.9≤x≤1.2, 0.6≤a≤0.99, 0.01≤b1+b2≤0.4, and -0.5≤z≤0.1 may be selected.

[0123] The positive electrode active material may further include a coating element or a doping element. For example, an element substantially the same as or similar to the auxiliary element may be used as the coating element or the doping element. For example, one or a combination of two or more of the above elements may be used as the coating element or the doping element.

[0124] The coating element or the doping element may be present on the surface of the lithium-nickel metal oxide particle or permeate through the surface of the lithium-nickel metal oxide particle and be included in the bonding structure represented by the Chemical Formula 1 or Chemical Formula 1-1.

[0125] The positive active material may include a nickel-cobalt-manganese (NCM)-based lithium oxide. In this case, the NCM-based lithium oxide having an increased nickel content may be used.

[0126] Ni can be provided as a transition metal related to the power and capacity of a lithium secondary battery. Thus, as described above, by using a high-content (high-Ni) composition for the positive electrode active material, a positive electrode with high capacity and a lithium secondary battery with high capacity can be provided.

[0127] However, as the Ni content increases, the long-term storage stability and life stability of the positive electrode or the secondary battery may be relatively reduced, and side reactions with the electrolyte may also increase. However, according to an exemplary embodiment, conductivity can be maintained by including Co, and life stability and capacity retention characteristics can be improved by Mn.

[0128] The content of Ni in the NCM-based lithium oxide (e.g., the mole fraction of Ni in the total moles of nickel, cobalt, and manganese) can be 0.6 or more, 0.7 or more, or 0.8 or more. In some embodiments, the content of Ni can be 0.8 to 0.95, 0.82 to 0.95, 0.83 to 0.95, 0.84 to 0.95, 0.85 to 0.95, or 0.88 to 0.95.

[0129] In some embodiments, the positive electrode active material may further include a lithium cobalt oxide-based active material, a lithium manganese oxide-based active material, a lithium nickel oxide-based active material, or a lithium iron phosphate (LFP)-based active material (e.g., LiFePO4).

[0130] In some embodiments, the positive electrode active material may include, for example, an Mn-rich-based active material, a Li rich layered oxide (LLO) / Over Lithiated Oxide (OLO)-based active material, or a Co-less-based active material having a chemical structure or crystal structure represented by Chemical Formula 2.

[0131] [Chemical Formula 2]

[0132] p[Li2MnO3]·(1-p)[Li q JO2]

[0133] In Chemical Formula 2, 0 < p < 1, 0.9 ≤ q ≤ 1.2, and J may include at least one element among Mn, Ni, Co, Fe, Cr, V, Cu, Zn, Ti, Al, Mg, and B.

[0134] For example, the positive electrode active material may be mixed in a solvent to prepare a positive electrode slurry. The positive electrode slurry may be coated on a positive electrode current collector and then dried and rolled to prepare a positive electrode mixture layer. The coating process may be performed by gravure coating, slot extrusion coating, multi-layer simultaneous die coating, stamping, doctor blade coating, dip coating, bar coating, casting, and the like, and is not limited thereto. The positive electrode mixture layer may further include a binder, and may optionally further include a conductive material, a thickener, and the like.

[0135] Non-limiting examples of the solvent used to prepare the positive electrode mixture include N-methyl-2-pyrrolidone (NMP), dimethylformamide, dimethylacetamide, N,N-dimethylaminopropylamine, ethylene oxide, tetrahydrofuran, and the like.

[0136] The binder may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (poly(vinylidene fluoride-co-hexafluoropropylene)), polyacrylonitrile, polymethyl methacrylate, nitrile rubber (NBR), polybutadiene rubber (BR), styrene butadiene rubber (SBR), etc. In one embodiment, a PVDF-based binder may be used as a positive electrode binder.

[0137] The conductive material may be added to enhance the conductivity of the positive electrode mixture layer and / or the mobility of lithium ions or electrons. For example, the conductive material may include carbon-based conductive materials such as graphite, carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, vapor-grown carbon fiber (VGCF), carbon fiber, and / or metal-based conductive materials such as perovskite materials such as tin, tin oxide, titanium oxide, LaSrCoO3, and LaSrMnO3, but is not limited thereto.

[0138] If necessary, the positive electrode mixture may further include a thickener and / or a dispersant, etc. As an embodiment, the positive electrode mixture may include a thickener such as carboxymethyl cellulose (CMC).

[0139] The negative electrode may include a negative electrode collector and a negative electrode mixture layer disposed on at least one side of the negative electrode collector.

[0140] Non-limiting examples of the negative electrode current collector include copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and the like. The thickness of the negative electrode current collector may be, for example, 10 - 50 µm, but is not limited thereto.

[0141] The negative electrode mixture layer may contain a negative electrode active material. As the negative electrode active material, a material capable of intercalating and deintercalating lithium ions may be used. For example, as the negative electrode active material, carbon-based materials such as crystalline carbon, amorphous carbon, carbon composites, and carbon fibers; lithium metal; lithium alloys; silicon (Si)-containing substances or tin (Sn)-containing substances may be used.

[0142] Examples of the amorphous carbon include hard carbon, soft carbon, coke, mesocarbon microbead (MCMB), mesophase pitch-based carbon fiber (MPCF), and the like.

[0143] Examples of the crystalline carbon include graphite-based carbons such as natural graphite, artificial graphite, graphitized coke, graphitized MCMB, and graphitized MPCF.

[0144] Examples of the lithium metal include pure lithium metal or lithium metal formed with a protective layer for suppressing dendrite growth and the like. In one embodiment, a lithium metal-containing layer deposited or coated on the negative electrode current collector may be used as the negative electrode active material layer. In one embodiment, a lithium thin film layer may be used as the negative electrode active material layer.

[0145] Examples of the elements contained in the lithium alloy include aluminum, zinc, bismuth, cadmium, antimony, silicon, lead, tin, gallium, or indium.

[0146] The silicon-containing substance may provide further enhanced capacity characteristics. The silicon-containing substance may contain Si, SiO x (0 < x < 2), metal-doped SiO x (0 < x < 2), silicon-carbon composites, and the like. The metal may contain lithium and / or magnesium, and metal-doped SiO x (0 < x < 2) may contain metal silicate.

[0147] (Method for manufacturing a negative electrode)

[0148] For example, the negative electrode active material may be mixed in a solvent to prepare a negative electrode slurry. The negative electrode slurry may be coated / deposited on a negative electrode current collector and then dried and rolled to prepare a negative electrode mixture layer. The coating process may be performed by gravure coating, slot extrusion coating, multi-layer simultaneous die coating, stamping, blade coating, dip coating, rod coating, casting, and the like, and is not limited thereto. The negative electrode mixture layer may further include a binder, and may optionally further include a conductive material, a thickener, and the like.

[0149] In some embodiments, the negative electrode may further include a negative electrode active material layer in the form of lithium metal formed by a deposition / coating process.

[0150] As non-limiting examples of the solvent for the negative electrode mixture, water, pure water, deionized water, distilled water, ethanol, isopropyl alcohol, methanol, acetone, n-propyl alcohol, tert-butyl alcohol, and the like may be cited.

[0151] As the binder, the conductive material, and the thickener, the above-mentioned substances that can be used when manufacturing the positive electrode can be used.

[0152] In some embodiments, the negative electrode binder may use styrene-butadiene rubber (SBR)-based binders, carboxymethyl cellulose (CMC), polyacrylic acid-based binders, polyethylenedioxythiophene (poly(3,4-ethylenedioxythiophene)) (PEDOT)-based binders, and the like.

[0153] According to an exemplary embodiment, an electrode assembly can be formed by repeatedly arranging a positive electrode, a negative electrode and a mixed separator. In some embodiments, the electrode assembly can be a winding type, a stacking type, a zigzag folding type, a stack-folding type.

[0154] The electrode assembly is housed in a case together with an electrolyte, thereby defining a lithium secondary battery. According to an exemplary embodiment, the electrolyte may use a non-aqueous electrolyte.

[0155] The non-aqueous electrolyte may include a lithium salt as an electrolyte and an organic solvent. The lithium salt may be, for example, Li + X - Indicates that, as the anion of the lithium salt (X - ), we can exemplify F - , Cl - Br - ,I - 、NO3 - 、N(CN)2 -, BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - etc.

[0156] The organic solvent may include an organic compound that has sufficient solubility for the lithium salt and additives and is not reactive in the battery. The organic solvent may include, for example, at least one of a carbonate-based solvent, an ester-based solvent, an ether-based solvent, a ketone-based solvent, an alcohol-based solvent, and an aprotic solvent. As the organic solvent, for example, propylene carbonate (PC), ethylene carbonate (EC), butylene carbonate, diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, dipropyl carbonate, vinylene carbonate, methyl acetate (MA), ethyl acetate (EA), n-propyl acetate (n-PA), 1,1-dimethylethyl acetate (DMEA), methyl propionate (MP), ethyl propionate (EP), fluoroethyl acetate (FEA), difluoroethyl acetate (DFEA), trifluoroethyl acetate (TFEA), dibutyl ether, tetraethylene glycol dimethyl ether (TEGDME), diethylene glycol dimethyl ether (DME), ether, DEGDME), dimethoxyethane, tetrahydrofuran (THF), 2-methyltetrahydrofuran, ethyl alcohol, isopropyl alcohol, dimethyl sulfoxide, acetonitrile, diethoxyethane, cyclopentane, γ-butyrolactone and propylene sulfite, etc. These can be used alone or in combination of two or more.

[0157] The non-aqueous electrolyte may further include an additive. The additive may include, for example, a cyclic carbonate-based compound, a fluorine-substituted carbonate-based compound, a sultone-based compound, a cyclic sulfate-based compound, a cyclic sulfite-based compound, a phosphate-based compound, and a borate-based compound.

[0158] The cyclic carbonate-based compound may include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), and the like.

[0159] The fluorine-substituted cyclic carbonate-based compound may include fluoroethylene carbonate (FEC) and the like.

[0160] The sultone-based compound may include 1,3-propane sultone, 1,3-propene sultone, 1,4-butane sultone, and the like.

[0161] The cyclic sulfate-based compound may include 1,2-ethylene sulfate, 1,2-propylene sulfate, and the like.

[0162] The cyclic sulfite-based compound may include ethylene sulfite, butylene sulfite, and the like.

[0163] The phosphate-based compound may include lithium difluoro bis-oxalato phosphate, lithium difluoro phosphate, and the like.

[0164] The borate-based compound may include lithium bis(oxalate) borate and the like.

[0165] The embodiments of the present invention are further described below with reference to specific experimental examples. The embodiments and comparative examples included in the experimental examples are only used to illustrate the present invention and are not used to limit the claims. Various modifications and variations can be made to the embodiments within the scope of the present invention and the technical concept, which is obvious to those skilled in the art, and it is natural that such modifications and variations belong to the scope of the claims.

[0166] Next, physical properties were evaluated as follows.

[0167] 1) Evaluation of haze

[0168] After the sample was placed in a 10×40×50 mm quartz cell and left at room temperature of 25°C for 12 hours, the haze was measured using a colorimeter (COH400, Nippon Denshoku Industries Co., Ltd.) and a halogen lamp (7027 Philips) with a rated voltage of 12 V and a power consumption of 50 W, which was vertically separated by 100 mm and fixed.

[0169] 2) Observe the phase at room temperature

[0170] The phases were visually observed at room temperature of 25°C and Figure 1 The phases are shown in FIG.

[0171] 3) Evaluation of battery performance

[0172] The temperature of the chamber containing the batteries manufactured in the embodiments and comparative examples was maintained at 25°C, and the constant current-constant voltage (CC-CV) of 4.2V was used to charge and discharge to 2.5V. The charge and discharge were measured by charging at 0.1C and discharging at 0.1C from 4.2V to 2.5V 20 times. The average value of the DC-IR impedance value of each cycle during the charge and discharge process was set as the resistance, and the resistance standard deviation was calculated based on each value.

[0173] 4) Nail penetration test

[0174] The battery was manufactured by the same method as in the embodiment and the comparative example, except that a 2Ah battery was manufactured by adjusting the number of stacked layers of the positive electrode, the negative electrode and the separator. The manufactured battery was charged to a residual capacity of 70-100% at a voltage of 4.2 V. A nail having a diameter of 3.0 mm was used to penetrate the center of the battery at a speed of 80 mm / sec to observe whether fire occurred. Figure 5 The photos show the unexploded and exploded scenes.

[0175] Furthermore, in the nail penetration experiment, the surface temperature was measured by a method of attaching a probe for measuring temperature on the electrode surface.

[0176] 5) Evaluation of flame retardancy

[0177] Using a small lighter, 1g of the mixed membrane manufactured in the embodiment was exposed to the flame, and then the time from the start of the fire to the end was measured to evaluate the flame retardancy. Afterwards, as a comparative example, the same amount of 1M LiPF6 carbonate-based electrolyte as the coating of the mixed membrane was impregnated in the same membrane substrate and the flame retardancy was evaluated (the ignition duration of the mixed membrane was 0 seconds, and the ignition duration of the comparative example was 23 seconds).

[0178] [Manufacturing Examples 1 to 10]

[0179] Succinonitrile was heated to 60°C to be melted, and then LiFSI was mixed at a weight ratio shown in Table 1 below, and then the phase was observed at room temperature of 25°C.

[0180] The haze was measured and is shown in Table 1 below.

[0181] [Table 1]

[0182]

[0183] As shown in Table 1, it was confirmed that, depending on the mixing ratio of succinonitrile and LiFSI, a liquid phase, a gel phase, or a solid phase was present at room temperature.

[0184] In the case of a solid phase or a gel phase, it was confirmed that when heated to 60°C or higher, it melted into a liquid phase, but when cooled again to a room temperature lower than 40°C, it returned to the original solid phase or gel phase.

[0185] Taking advantage of this, when coating on the diaphragm, the diaphragm is coated with a solid state having different LiFSI contents on both sides. When manufacturing the battery, when heated to above 60°C, it is confirmed that the succinonitrile and LiFSI coated on both sides satisfy a specific content ratio as shown in Manufacturing Examples 3 to 9 of Table 1, and therefore can be maintained in a liquid or gel state at room temperature.

[0186] Furthermore, as shown in the above-mentioned Production Examples 3 to 9, it was confirmed that when the battery was in the gel phase or the liquid phase at room temperature, the battery capacity at room temperature was exhibited.

[0187] The present invention is more specifically illustrated by the following examples.

[0188] [Example 1]

[0189] <Preparation of coating solution (1) for forming first functional layer>

[0190] 50 g of succinonitrile was heated to 60° C. to be melted into a liquid phase, thereby preparing a coating liquid (1).

[0191] <Preparation of coating solution (2) for forming second functional layer>

[0192] 50 g of succinonitrile was heated to 60° C. to be melted, and then 50 g of LiFSI was added to prepare a coating liquid ( 2 ).

[0193] <Manufacturing of Hybrid Separator>

[0194] As a porous substrate, a polyimide nonwoven fabric having a thickness of 20 μm and a porosity of 42% was prepared.

[0195] The coating liquid (1) is coated on one side of the polyimide nonwoven fabric at 60° C. so that the coating liquid (1) remains in a liquid phase, and then cooled to room temperature and dried to form a solid first functional layer.

[0196] Furthermore, the coating liquid (2) was applied to the other side of the polyimide nonwoven fabric at 60° C. to keep the coating liquid (2) in a liquid phase, and then cooled to room temperature and dried to form a solid second functional layer.

[0197] The coating weights of the first functional layer and the second functional layer are 3.87 g / m 2 .

[0198] <Battery Manufacturing>

[0199] Preparation of positive electrode: 94 wt% LiCoO2, 2.5 wt% polyvinyl fluoride, and 3.5 wt% carbon black were added to N-methyl-2-pyrrolidone (NMP) and stirred to prepare positive electrode slurry. The slurry was coated on an aluminum foil with a thickness of 30 μm, and rolled after drying at a temperature of 120°C to manufacture a positive electrode plate with a thickness of 150 μm.

[0200] Negative electrode preparation: 95 wt% of artificial graphite, 3 wt% of acrylic latex (trade name: BM900B, solid content: 20 wt%) with a Tg of -52°C, and 2 wt% of carboxymethylcellulose (CMC) were added to water and stirred to prepare a negative electrode slurry. The slurry was coated on a copper foil with a thickness of 20 μm, dried at a temperature of 120°C, and then rolled to prepare a negative electrode plate with a thickness of 150 μm.

[0201] Battery production: Using the positive electrode, negative electrode and mixed separator produced above, a soft-pack type battery was assembled in a stacked manner to produce an 80 mAh soft-pack type lithium-ion secondary battery. The produced battery was left at 60° C. for 1 hour before use.

[0202] The physical properties of the manufactured batteries were evaluated and are shown in Table 2 below. In addition, Table 3 shows the nail penetration test of the batteries.

[0203] [Example 2]

[0204] The same method as in Example 1 was carried out except that the composition of the following coating solution was changed.

[0205] <Preparation of coating solution (1) for forming first functional layer>

[0206] 50 g of succinonitrile was heated to 60° C. to be melted into a liquid phase, and then mixed with 2.5 g of fluoroethylene carbonate (FEC) to prepare a coating liquid (1).

[0207] <Preparation of coating solution (2) for forming second functional layer>

[0208] 50 g of succinonitrile was heated to 60° C. to be melted, and then 5 g of fluoroethylene carbonate (FEC) and 50 g of LiFSI were added to prepare a coating liquid ( 2 ).

[0209] <Manufacturing of Hybrid Separator>

[0210] As a porous substrate, a polyimide nonwoven fabric having a thickness of 20 μm and a porosity of 42% was prepared.

[0211] The coating liquid (1) is coated on one side of the polyimide nonwoven fabric at 60° C. so that the coating liquid (1) remains in a liquid phase, and then cooled to room temperature and dried to form a solid first functional layer.

[0212] Furthermore, the coating liquid (2) was applied to the other side of the polyimide nonwoven fabric at 60° C. to keep the coating liquid (2) in a liquid phase, and then cooled to room temperature and dried to form a solid second functional layer.

[0213] The coating weights of the first functional layer and the second functional layer are 3.87 g / m 2 .

[0214] The physical properties of the manufactured batteries were evaluated and are shown in Table 2 below. In addition, Table 3 shows the nail penetration test of the batteries.

[0215] [Example 3]

[0216] A battery was manufactured by the same method as in Example 2 except that the contents of fluoroethylene carbonate (FEC) in the coating liquids (1) and (2) were changed and used as shown in Table 2 below. The physical properties of the manufactured batteries were evaluated and are shown in Table 2 below.

[0217] [Example 4 to Example 9]

[0218] A battery was manufactured by the same method as in Example 2, except that the contents of succinonitrile and LiFSI in the coating liquids (1) and (2) were changed and used as shown in Table 2 below. The physical properties of the manufactured batteries were evaluated and are shown in Table 2 below.

[0219] [Comparative Example 1]

[0220] The positive electrode and the negative electrode were manufactured by the same method as in Example 1.

[0221] A polyimide nonwoven fabric with a thickness of 20 μm and a porosity of 42% is used as a separator between the positive electrode and the negative electrode and a soft-pack battery is assembled in a stacked manner. An electrolyte of ethylene carbonate / ethyl methyl carbonate / dimethyl carbonate (volume ratio of 3:5:2) in which 1M lithium hexafluorophosphate (LiPF6) is dissolved is injected into the assembled battery to manufacture a soft-pack lithium-ion secondary battery with a capacity of 80 mAh. The electrolyte used is in a liquid phase at room temperature, and the measured haze is 0%.

[0222] The physical properties of the manufactured batteries were evaluated and are shown in Table 2 below. In addition, Table 3 shows the nail penetration test of the batteries.

[0223] [Comparative Example 2]

[0224] A battery was manufactured by the same method as in Example 2, except that the contents of succinonitrile and LiFSI in the coating liquids (1) and (2) were changed and used as shown in Table 2 below. The physical properties of the manufactured batteries were evaluated and are shown in Table 2 below.

[0225] [Table 2]

[0226]

[0227] In Table 2, in Examples 1 to 3, the first functional layer and the second functional layer are the same final mixing ratio after changing the content of lithium salt and heating at 60°C for 1 hour after solid phase coating, and the result of changing the content of FEC is that the capacity of the battery measured at room temperature is also shown in Example 1 without using FEC, and more preferably, as shown in Example 2, when the content of FEC used is less than 5% by weight, it is confirmed that the battery capacity is further improved. In addition, in the case of Example 2, although a separate liquid electrolyte is not injected, it shows a battery capacity similar to that of Comparative Example 1 injected with a liquid electrolyte. As shown in Example 3, when the content of FEC used is 10% by weight, it is confirmed that the battery capacity is reduced compared with Example 2.

[0228] In addition, as shown in Examples 4 to 9, the composition ratio of the first functional layer was maintained, and the coating amount was adjusted and coated so that the final mixing weight ratio was 2: 1 to 7: 1. As a result, it was confirmed that the battery capacity was expressed, and the battery capacity was higher in the liquid phase than in the gel phase.

[0229] On the other hand, in the case of Comparative Example 2, the battery capacity could not be confirmed at room temperature, but the battery capacity could be confirmed in the state maintained at 60°C.

[0230] [Table 3]

[0231]

[0232] As shown in Table 3, in Examples 1 and 2 using the hybrid separator according to one embodiment of the present invention, it was confirmed that no explosion occurred even at a 100% charge state. However, in Comparative Example 1, it was confirmed that an explosion occurred at a charge state of 80% or more.

[0233] Using a small lighter, 1g of the mixed membrane was exposed to a flame, and then the time from the start of the fire to the end was measured to evaluate the flame retardancy. Afterwards, as a comparative example, the same membrane substrate was impregnated with the same amount of 1M LiPF6 carbonate-based electrolyte as the coating of the mixed membrane and the flame retardancy was evaluated. At this time, the mixed membrane did not catch fire due to its flame retardant properties, so the ignition duration was 0 seconds. In comparison, the ignition duration of Comparative Example 1 was 23 seconds.

[0234] As described above, the present invention has been described through specific contents and limited embodiments, but this is only provided to help a more comprehensive understanding of the present invention. The present invention is not limited to the above embodiments, and technicians in the field of the present invention can make various modifications and variations through such descriptions.

[0235] Therefore, the above-described contents are merely examples of applying the principles of the present invention, and other configurations may be further included without departing from the scope of the present invention.

Claims

1. A hybrid diaphragm comprising: Porous substrates; A first functional layer, the first functional layer is formed by coating a single nitrile compound or a mixture of a nitrile compound and a lithium salt on one side of the porous substrate, and the first functional layer is a solid phase; as well as a second functional layer, the second functional layer being formed by coating a mixture of a nitrile compound and a lithium salt on the other surface of the porous substrate, and the second functional layer being in a solid phase, The contents of the lithium salt in the first functional layer and the second functional layer are different from each other.

2. The hybrid membrane according to claim 1, wherein: The first functional layer and the second functional layer are formed by filling the surface and pores of the porous substrate.

3. The hybrid membrane according to claim 1, wherein: The first functional layer and the second functional layer are in a solid phase at room temperature, but when heated, the solid first functional layer and the second functional layer melt and mix and undergo a phase change, thereby maintaining a liquid phase or a gel phase also at room temperature.

4. The hybrid membrane according to claim 3, wherein: After the phase change sample is placed in a quartz cell of 10×40×50mm and left at room temperature for 12 hours, the haze is measured using a colorimeter at a vertical distance of 100mm from a halogen lamp with a rated voltage of 12V and a power consumption of 50W. The haze of the liquid phase is less than 50%, the haze of the gel phase is more than 50% and less than 90%, and the haze of the solid phase is more than 90%.

5. The hybrid membrane according to claim 1, wherein: The nitrile compound is solid at room temperature or can exist as a solid at room temperature when mixed with a lithium salt, and the nitrile compound is a compound containing one or more -C≡N functional groups.

6. The hybrid membrane according to claim 5, wherein: The nitrile compound which is solid at room temperature is selected from any one or a mixture of two or more of succinonitrile (SN), (3,4-dimethoxyphenyl)acetonitrile, 2-(4-bromo-2-methoxyphenyl)acetonitrile, 2-fluorophenylacetonitrile, 2-chloro-4-fluorophenylacetonitrile and 4-fluorophenylacetonitrile, The nitrile compound that can exist as a solid at room temperature when mixed with a lithium salt is any one selected from glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile, sebacatenitrile, undecane dinitrile, and dodecanedinitrile, or a mixture of two or more thereof.

7. The hybrid membrane according to claim 1, wherein: The lithium salt is selected from LiTFSI ((CF3SO2)2NLi), LiFSI ((SO2F)2NLi), (C2F5SO2)2NLi, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)3CLi, LiBF2(C2O4), LiAlO2 and LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2) in any one or more forms, wherein x and y are natural numbers.

8. The hybrid membrane according to claim 1, wherein: The total content of the nitrile compound used in the first functional layer and the second functional layer is such that when mixed with the lithium salt, a liquid phase or a gel phase is maintained at room temperature.

9. The hybrid membrane according to claim 1, wherein: The first functional layer is formed by impregnation on the surface and the first side of the porous substrate and is formed to be 0.5-10 g / m 2 , The second functional layer is formed by impregnation on the surface and the second side of the porous substrate and is formed to be 0.5-10 g / m 2 .

10. The hybrid membrane according to claim 1, wherein: The porous substrate is formed by laminating any one selected from a porous film, a nonwoven fabric and a woven fabric, or two or more thereof.

11. The hybrid membrane according to claim 1, wherein: The thickness of the porous substrate is 1-80 μm.

12. The hybrid membrane according to claim 1, wherein: The first functional layer and the second functional layer further include less than 5 wt % of a carbonate-based additive.

13. An electrochemical device comprising the hybrid separator according to any one of claims 1 to 12, in, By setting the hybrid membrane and heating it, the first functional layer and the second functional layer included in the hybrid membrane are liquefied and mixed with each other and undergo phase change, thereby existing as a phase change layer in a liquid phase or a gel phase at room temperature.

14. The electrochemical device according to claim 13, wherein: The capacity of the electrochemical device is greater than 50 mAh.

15. A method for manufacturing a hybrid membrane, comprising the steps of: A solid-phase nitrile compound alone or a solid-phase mixture of a nitrile compound and a lithium salt is heated to be melted and coated on the first surface of the porous substrate so as to be impregnated into the surface and the inside of the pores, and then cooled to form a solid-phase first functional layer; as well as The solid phase mixture of the nitrile compound and the lithium salt is heated to be melted and coated on the second surface of the porous substrate so as to be impregnated into the surface and the inside of the pores, and then cooled to form a solid second functional layer. The contents of the lithium salt in the first functional layer and the second functional layer are different from each other.

16. The method for manufacturing a hybrid membrane according to claim 15, wherein: The first functional layer and the second functional layer are in a solid phase at room temperature, but when heated, the solid first functional layer and the second functional layer melt and mix and undergo a phase change, thereby maintaining a liquid phase or a gel phase also at room temperature.

17. The method for manufacturing a hybrid membrane according to claim 15, wherein: The first functional layer and the second functional layer further include less than 5 wt % of a carbonate-based additive.